Localized Giant Cell Tenosynovial Tumor Seen in the Knee Joint. (4th March 2014) - Beytemür, Ozan; Albay, Cem; Tetikkurt, Ümit Seza; Öncü, Mehmet; Baran, Mehmet Ali; Çağlar, Sever; Güleç, Mehmet Akif
Abstract : Tenosynovial giant cell tumor is a locally aggressive tumor arising from the synovia of the fibrous tissue surrounding the joints, tendon sheaths, mucosal bursas, and tendons. Although it is often to be observed at the hand, localized form is very rare in the knee joint. In this case report, we aimed to present a very rare case of a surgically treated intra-articular giant cell tenosynovial tumor arising from the hoffa's infrapatellar fat pad of a 19-year-old male patient, by reviewing the literature. The patient we have treated with marginal excision was asymptomatic at the 14th month in the controls and recurrence was not detected.